Hydrocracking of Waste Palm Cooking Oil into Hydrocarbon Compounds over Mo Catalyst Impregnated on SBA-15 - Alisha, Gesha Desy (Springer Science and Business Media B.V., 2022)
The highest activity and selectivity results were achieved in the presence of Mo metal supported by SBA-15. Mo/SBA-15 catalyst was synthesized using the wet impregnation method. Catalysts were characterized using FTIR, XRD, Surface Area Analyzer (SAA), and SEM-EDX. Mo/SBA-15 has pore diameters, surface area, and Mo metal concentration of 561.4 m2/g, 6.53 nm, and 4.41%, respectively. The hydrocracking process was carried out at a temperature of 500 °C with a ratio of catalyst: feed weight 1: 100. The best catalyst for hydrocracking of waste palm cooking oil was Mo/SBA-15. The presence of Mo metal is role play in the hydrocracking process because it can increase the activity and selectivity of the catalyst. In addition, decreased pore diameter and surface area also affect the hydrocracking process. The total liquid product produced by the Mo/SBA-15 catalyst was 53.86 wt.%. The results of the conversion of liquid products analyzed using GC-MS showed a total hydrocarbon compound of 50.35 wt.%. The fraction of gasoline produced was 42.46 wt.% and the fraction of diesel fuel produced was 7.89 wt.%.